IDNLearn.com provides a user-friendly platform for finding and sharing knowledge. Our experts are available to provide accurate, comprehensive answers to help you make informed decisions about any topic or issue you encounter.

Solve for [tex]\( x \)[/tex]:

[tex]\[ (x+4) = (5x + 2) \][/tex]


Sagot :

Sure, let's solve the given equation step by step.

We've been given the equation:
[tex]\[ x + 4 = 5x + 2 \][/tex]

Let’s solve for [tex]\( x \)[/tex] by isolating it on one side of the equation.

1. Start by eliminating the [tex]\( x \)[/tex] term on the right side of the equation.

Subtract [tex]\( x \)[/tex] from both sides of the equation:
[tex]\[ x + 4 - x = 5x + 2 - x \][/tex]
This simplifies to:
[tex]\[ 4 = 4x + 2 \][/tex]

2. Next, isolate the term with [tex]\( x \)[/tex] by eliminating constants on the right side.

Subtract 2 from both sides of the equation:
[tex]\[ 4 - 2 = 4x + 2 - 2 \][/tex]
This simplifies to:
[tex]\[ 2 = 4x \][/tex]

3. Solve for [tex]\( x \)[/tex] by dividing both sides by the coefficient of [tex]\( x \)[/tex], which is 4.
[tex]\[ \frac{2}{4} = \frac{4x}{4} \][/tex]
Simplifies to:
[tex]\[ \frac{1}{2} = x \][/tex]

Thus, the solution to the equation [tex]\( x + 4 = 5x + 2 \)[/tex] is:
[tex]\[ x = \frac{1}{2} \][/tex]